Behavior of coffee cultivars under the incidence of diseases of rust and gray leaf spot in two cultivation environments - Carvalho, Alex Mendonça; Cardoso, Diego Abreu; Carvalho, Gladyston Rodrigues; Carvalho, Vicente Luiz; Pereira, Antonio Alves; Ferreira, André Dominghetti; Carneiro, Leandro Flávio (Coffee Science - ISSN 1984-3909, 2017)
Orange rust, caused by Hemileia vastatrix, is the main coffee disease in terms of scope and damage. The development of cultivars, resistant and/or tolerant to pests and diseases, has an important role in the productivity increase and production cost decrease. Thus, the aim of this study was to provide information about the reaction of ten commercial cultivars of C. Arabica to the incidence of rust and gray leaf spot in two important coffee regions of Minas Gerais state. The experiments were carried out in two important coffee regions of Minas Gerais (Southern Minas and Alto Paranaiba), being implemented in public experimental areas in the Experimental Farm of the Agricultural Research Company of Minas Gerais (Epamig) in Patrocinio-MG and Experimental Campus of the Federal University (Ufla) of Lavras-MG. The experimental design was of randomized blocks with three replicates and 10 plants per plot, when only six central plants were considered as a useful part. The adopted spacing was of 3.5 m between rows x 0.70 m between plants. Evaluations of both rust incidence and severity as well as gray leaf spot incidence were carried out monthly from January to August each year (2011/2012 and 2012/2013 crops). The incidence percentages of the disease were transformed into area below the incidence and rust severity (AACPIF, AACPSF) and gray leaf spot incidence (AACPIC) progress curve, according to criteria established by Campbell and Madden (1990). The Oeiras cultivar presents total loss of resistance to rust, Catiguá MG2 cultivar presents immunity to the rust pathogen and the cultivars studied exhibit no resistance to gray leaf spot.